Molecular Characterization and Pathogenicity of Staphylococcus aureus Isolated from Benin-City, Nigeria - Osahon Obasuyi; JoAnn McClure; Francis E. Oronsaye; John O. Akerele; John Conly; Kunyan Zhang (Microorganisms, 2020)
While numerous studies examine the epidemiology and molecular characterization of Staphylococcus aureus in most developed countries, the detailed molecular characterization and molecular epidemiology of S. aureus strains and clones in Africa is lacking. We determined the molecular epidemiology and virulence of 81 non-duplicate isolates of S. aureus from Benin-City, Nigeria, collected during January–July 2016, and compared with global strains. Forty-seven isolates (58.0%) were found to be methicillin-sensitive Staphylococcus aureus (MSSA), while 34 (42.0%) were methicillin-resistant Staphylococcus aureus (MRSA). ST152-MSSA (24.7%) and ST7-MRSA-V (19.8%) were the dominant groups identified, which were not genetically related to global predominant strains, but rather exhibited regional dominance. An interesting finding of the study was the presence of highly related strains in the region, which differed primarily in their methicillin resistance gene carriage, staphylococcal cassette chromosome mec (SCCmec), with 99.4–99.7% relatedness between the genomes of the strains within the MRSA–MSSA pairs. This suggests that the strains within a pair are experiencing gain or loss of SCCmec within local conditions, with evolution continuing to diversify the strains to a small degree. This study represents the most comprehensive genetic and virulence study of S. aureus in Nigeria.